Spectral theory and applications - Girouard, Alexandre, 1976- (Contemporary mathematics (American Mathematical Society). Centre de recherches mathématiques proceedings, 2018)
This book is a collection of lecture notes and survey papers based on the minicourses given by leading experts at the 2016 CRM Summer School on Spectral Theory and Applications, held from July 4-14, 2016, at Université Laval, Québec City, Québec, Canada. The papers contained in the volume cover a broad variety of topics in spectral theory, starting from the fundamentals and highlighting its connections to PDEs, geometry, physics, and numerical analysis.